Evaluation of curettage, synthetic bone grafting and fixation with implant in benign osteolytic and cystic lesions of long bones in children and young adults - Ghosh, Tapas Kumar; Banik, Rajeeb; Bhattacharjya, Bijoy (International Journal of Research in Orthopaedics, 2019)
Background: Curettage is one of the most common treatment options for benign lytic bone tumors and cystic lesions. In children and young adults, the resultant defect is usually filled with synthetic bone graft, which is a natural calcium phosphate hydroxyappatite (HA) in crystalline ceramic form. Methods: Sixteen cases of benign lytic and cystic lesions of bone were managed by simple curettage and grafting using hydroxyappatite blocks. Displaced pathological fractures or impending peritrochanteric fractures were fixed by implant. Commercially available HA was used for this purpose. Mean duration of follow up was 17.5 months (range 12 –30 months). Mean patient age was 11.2 years (range 6–20 years). Radiological staging of graft incorporation was done as per criteria of Irwin et al. Results: Among 16 cases, 2 patients presented with non-ossifying fibroma and 2 patients with simple bone cyst, 12 cases were aneurysmal bone cyst. 5 patients had pathological fracture. Healing of lesion and graft incorporation is seen in all of the cases. At 6 months of follow up 3 cases were in Irwin stage III, 9 cases were in Irwin stage II and 4 cases were in Irwin stage I. At final follow up 10 cases were in Irwin stage III and rest was in Irwin stage II. No recurrence seen till date. Conclusions: We conclude that meticulous curettage and filling of bone cavity by calcium phosphate hydroxyappatite and fixation with implant in displaced pathological fracture or impending fracture is the procedure of choice of management of benign lytic lesions of bone.